Link between mast cells and bacteria: Antimicrobial defense, function and regulation by cytokines. (September 2017) - Conti, Pio; Carinci, Francesco; Caraffa, Alessandro; Ronconi, Gianpaolo; Lessiani, Gianfranco; Theoharides, Theoharis C.
Abstract: Bacteria and their products, such as LPS, act on mast cells (MCs) to induce the secretion of multiple cytokines, including IL-1, TNF, IL-18 and IL-33, which can be dosed in the site of infected tissues. Antigen-binding IgE cross-links FcεRI on mast cells involves the generation and activation of PKCδ, ERK, tyrosine kinases ( Syk and Lyn ) and mitogen-activated protein kinases (MAPKs), inducing the release of chemical mediators which provoke inflammation and hypersensitive reaction. Other stimuli, including, cytokines, neuropeptides, chemical and physical activators, can also act on MCs to release a plethora of inflammatory compounds. Activated MCs produce a broad spectrum of inflammatory cytokines, chemokines, lipid compounds and vasoactive amines, all involved in immune response. By producing TNF, MCs have an antibacterial defense and a protective function; while pathogenic bacteria and their products, such as LPS, have an inflammatory response through MC activation. LPS binding TLR4 produce MC generation IL-1 family members, and chemokines, which may recruit inflammatory cells at the infection site; whereas in Kit W/W-v mice, where MCs are genetically absent, the inflammatory effect is not present. We report for the first time a link between MCs and bacteria emphasizing the mediation of inflammatory cytokines/chemokines. We can conclude that mast cells fight bacteria, and their immune response is perfectly integrated in the immune network. We hope that the understanding of microbial and mast cell interaction leads to more efficient therapeutic development in relation to microbial resistance.